2017
DOI: 10.18632/oncotarget.15242
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular longitudinal strain in soccer referees

Abstract: Along the years, the analysis of soccer referees perfomance has interested the experts and we can find several types of studies in literature using in particular cardiac imaging. The aim of this retrospective study was to observe relationship between VO2max uptake and some conventional and not-conventional echocardiographic parameters. In order to perform this evaluation, we have enrolled 20 referees, belonging to Italian Soccer Referees' Association and we have investigated cardiovascular profile of them. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
1
9
2
Order By: Relevance
“…Another study enrolling older soccer referees found a direct relationship between LV longitudinal deformation and VO 2 /kg. 6 Our findings suggest that LV and LA morphology correlate directly, while resting functional parameters have inverse relationships with peak exercise capacity in mixed trained athletes. Our second multivariate linear regression model revealed that RV morphology and function (i.e., RVEDVi, RV FWLS) are also independent predictors of VO 2 /kg besides the parameters that were revealed in our first model.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Another study enrolling older soccer referees found a direct relationship between LV longitudinal deformation and VO 2 /kg. 6 Our findings suggest that LV and LA morphology correlate directly, while resting functional parameters have inverse relationships with peak exercise capacity in mixed trained athletes. Our second multivariate linear regression model revealed that RV morphology and function (i.e., RVEDVi, RV FWLS) are also independent predictors of VO 2 /kg besides the parameters that were revealed in our first model.…”
Section: Discussionmentioning
confidence: 56%
“…1,4 Despite the pronounced cardiac remodeling in athletes, it is still a matter of debate whether exercise capacity can be predicted by cardiac size or by resting functional measurements. [5][6][7] Traditionally, the left ventricle (LV) is the main focus of physiologic and clinical cardiovascular research, but the importance of left atrial (LA) structure and mechanics should not be underestimated. Detailed assessment of LA morphology and function provides additive data in various cardiovascular diseases.…”
mentioning
confidence: 99%
“…Corroborating with our data, other authors reported moderate values of VO 2 max, ranging from 44 to 56 ml•kg -1 •min -1 . 1,3,4,27,30 This result can be explained by the fact that referees do not need to significantly increase their VO 2 max during matches to obtain better performance, reaching the maximum value of 50 ml•kg -1 •min -1 in 90 min. 1 Thus, the capixabas referees presented good physical fitness related to health and physical performance, which makes them eligible to work in different leagues and/or championships.…”
Section: Good Excellentmentioning
confidence: 94%
“…[2][3][4]12,26 In agreement with previous studies, resting ECG demonstrated this characteristic in the referees of the present study. 27,28 In the evaluation during effort, the sample showed satisfactory values of reserve HR and increase of resting HR to HR at the point of maximum effort, considered an important predictor of cardiovascular diseases and sudden death. 29 In addition, all the capixabas referees were classified into the fair (10%), good (50%), and excellent (40%) categories.…”
Section: Good Excellentmentioning
confidence: 96%
“…In particular, many studies have attempted to measure their level of performance by means of VO2 maximal uptake [3][4][5] and/or results of fitness field tests [6] and laboratory test [7,8]. Over the years, findings obtained in research applied to soccer refereeing have allowed consistent improvements in terms of training methods and/or types of tests evaluating fitness and/or specific physical skills [9,10].…”
Section: Introductionmentioning
confidence: 99%